Medical Effects and Dosimetric Data from Nuclear Tests at the Semipalatinsk Test Site - Balmukhanov, S. B. (2006)
In the former Soviet Union, two sites were used for most surface or atmospheric nuclear tests. One of these was at Novaya Zemlya in the arctic, but the earlier and more used of the two was in what is now the Republic of Kazakhstan. The Semipalatinsk Test Site (STS), or Polygon as it was called, was instituted in 1947. Data relating to the radiation levels were declassified in 1992 and are published in the first two tables of this report. Basically, the population was exposed to three sources of radiation: acute external gamma irradiation as the plume from the explosion passed over the areas; external gamma (and probably beta) irradiation from the fallout as it settled on the ground and the people themselves; and internal gamma, beta, and small amounts of alpha irradiation. Medical examinations conducted under this report and compared with data from previous expeditions have shown a significant disparity in health status between inhabitants of villages in the immediate neighborhood of the STS and inhabitants of similar settlements remote from the STS. The original document contains color images.